Exploring the Effects of Meditation Techniques Used by Mindfulness-Based Programs on the Cognitive, Social-Emotional, and Academic Skills of Children: A Systematic Review - Filipe, Marisa G.; Magalhães, Sofia; Veloso, Andreia S.; Costa, Ana Filipa; Ribeiro, Lúcia; Araújo, Patrícia; Castro, São Luís; Limpo, Teresa (Frontiers in Psychology, 2021)
There is evidence for the positive impact of mindfulness in children. However, little is known about the techniques through which mindfulness practice results in differential outcomes. Therefore, this study intended to systematically review the available evidence about the efficacy of meditation techniques used by mindfulness-based programs on cognitive, socio-emotional, and academic skills of children from 6 to 12 years of age. The review was registered on the PROSPERO database, and the literature search was conducted according to PICO criteria and PRISMA guidelines. The EBSCO databases were searched, and 29 studies were eligible: nine randomized controlled trials and 20 quasi-experimental studies. All the included randomized controlled trials were rated as having a high risk of bias. Overall, the evidence for mindfulness techniques improving cognitive and socio-emotional skills was reasonably strong. Specifically, for cognitive skills, results showed that all the interventions used “body-centered meditations” and “mindful observations.” Regarding socio-emotional skills, although all the studies applied “body-centered meditations” and “mindful observations,” “affect-centered meditations” were also frequent. For academic skills, just one quasi-experimental trial found improvements, thus making it difficult to draw conclusions. Further research is crucial to evaluate the unique effects of different meditation techniques on the cognitive, social-emotional, and academic skills of children. Systematic Review Registration: Identifier: RD42019126767.